Challenges faced by migrant seasonal agricultural farmworkers for food accessibility in Spain: A qualitative study - Luis Alejandro Rodríguez-Guerrero; José Tomás Mateos; Iratxe Pérez-Urdiales; Mar Jiménez-Lasserrotte; Juan Agustín González; Erica Briones-Vozmediano (Global Public Health)
Migrants who work seasonally in agriculture face living and working conditions that significantly impact their health. Some of these conditions are related to inadequate food access or food preservation and preparation hygiene. This study aimed to explore how migrant and seasonal agricultural farmworkers access food in Spain from the perspective of professionals supporting this population. We conducted a qualitative study in 2021 based on semistructured interviews with 92 social and health service professionals involved in the care of seasonal migrant workers in 4 Spanish provinces. We identified three themes through reflective thematic analysis: (1) Access to food depends on NGOs and institutions, especially after the COVID-19 pandemic; (2) Relevant cultural differences in diet depending on North African or sub-Saharan origin; (3) Seasonal migrant workers frequently suffer from nutritional and other health problems related to food security. The professionals interviewed described the diet of seasonal migrant workers as based on food with little variety, insufficient protein content, and obesogenic products. They also reported a generalized lack of hygiene in food storage and preparation. This study calls for encouraging dietary support strategies to reduce challenges in food accessibility, which would prevent health problems in this population and bring them social justice.